EVALUASI PROGRAM MAGANG PADA PENYELENGGARAAN PENDIDIKAN SMK DENGAN MODEL (3+1) PROGRAM KEAHLIAN KEHUTANAN DI SMK NEGERI 1 PAGELARAN – CIANJUR (Implementasi Model CIPPO) - Mulyadi, Yadi (Jurnal Evaluasi Pendidikan, 2018)
This study aims to determine the product and outcomes of the apprenticeship program on the implementation of vocational education with model (3 + 1) in the Forestry Expertise Program at SMK Negeri 1 Pagelaran Cianjur. The research evaluation used CIPPO evaluation model. The research approach used descriptive qualitative techniques. In this study the data collecting techniques included interviewes, documentation studies, observations, quantitative descriptive research, and questionnaire. The result of the research shows that in general the apprenticeship program on vocational education with model (3 + 1) runs well and in accordance with the purpose of vocational secondary education to prepare graduates who have competence in accordance with the needs of DU/DI, so that the presence of apprenticeship program is still needed but must be appropriate with the curriculum set by the government. Implementation of the apprenticeship program at the Forestry Expertise Program at SMK Negeri 1 Pagelaran Cianjur is relevant to the KTSP Curriculum due to the 4-year study period, and is less relevant to the 2013 curriculum due to the 3-year study period. Therefore, the implementation of the apprenticeship program in the spectrum of 2013 curriculum can be implemented by changing the time of apprenticeship in the third year or to be maintained in the fourth year with the adjustment of study period at Forestry Technology Expertise Competency of Forest Product Processing Technology in Spectrum of 2013 curriculum back to 4 years